2020
DOI: 10.3390/nu12020383
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation and Use of a Food Frequency Questionnaire Among the Population in Trivandrum, South Kerala, India

Abstract: Dietary record tools such as food frequency questionnaire (FFQ) and food diaries (FD) are the most commonly used choices for assessing dietary intakes in most large-scale epidemiological studies. The authors developed a self-administered 360-item food frequency questionnaire (FFQ) to assess dietary intakes amongst a population-based cohort in South Kerala. In the validation study (n = 460), the data were collected using FFQs that were administered on three different occasions which were then compared to 7-day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Another explanation is that the participants lacked knowledge of what food items they should register when they were eating prepared dishes. Our estimated correlation coefficient of rho = 0.65 was in agreement with estimates from other studies validating fiber intakes by using other types of dietary assessment methods against dietary records; correlation coefficients ranging from 0.43 to 0.72 have been identified [ 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 ]. In some studies, the correlation coefficients increased when adjusting for energy intakes [ 18 , 24 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another explanation is that the participants lacked knowledge of what food items they should register when they were eating prepared dishes. Our estimated correlation coefficient of rho = 0.65 was in agreement with estimates from other studies validating fiber intakes by using other types of dietary assessment methods against dietary records; correlation coefficients ranging from 0.43 to 0.72 have been identified [ 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 ]. In some studies, the correlation coefficients increased when adjusting for energy intakes [ 18 , 24 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our estimated correlation coefficient of rho = 0.65 was in agreement with estimates from other studies validating fiber intakes by using other types of dietary assessment methods against dietary records; correlation coefficients ranging from 0.43 to 0.72 have been identified [ 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 ]. In some studies, the correlation coefficients increased when adjusting for energy intakes [ 18 , 24 , 26 , 27 ]. Energy adjustment was not possible in our study since the application did not target the totality of the diet and thereby lacks the necessary information.…”
Section: Discussionsupporting
confidence: 89%
“…Trivandrum (Thiruvananthapuram) is the southern-most district in the state of Kerala, located on the south-west coast of India. At the time of the Indian census in 2011, it had a population of 3.3 million divided into urban and rural domiciles (urban 54%, rural 46%) [ 25 ]. The Trivandrum NAFLD cohort was originally designed and set up in 2013 to examine the interaction between genetics and lifestyles factors that result in increased risk of NAFLD within this population.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary data for this study were collected by trained nutritionists using the Population Health and Research Institute (PHRI) food frequency questionnaires (FFQs), which were validated against three-day food records, and self-reported 24-h recalls [ 25 ]. The PHRI-FFQ consists of 361 recipes and 28 single food items (Indian foods) in 13 sections and is designed to classify participants according to the average daily intake level of energy, nutrients, and food items/recipes during the past one year.…”
Section: Methodsmentioning
confidence: 99%
“…FFQs offer useful information about the dietary intake and the relationship between it and the health and disease outcomes [11]. Due to their ease of administration, low burden on participants and staff, and lower cost compared to other assessment techniques, FFQs have been widely used in large population-based studies [12]. In total, 814 LD-independent loci (defined as >500 kb apart) were identified that surpassed genome-wide significance (p < 5.0 × 10 −8 ).…”
Section: Gwas Summary Data Of Dietary Habitsmentioning
confidence: 99%